Geophysical-Hydrogeological study using Electromagnetic Methods in the municipality of Valverde del Fresno, Spain - Zevallos Flores, Arturo Santos (2022)
A geophysical and hydrogeological investigation was carried out to determine the lithology and morphology of the materials that make up the area of the municipality of Valverde del Fresno, Spain. To characterize the existing geoelectric units in the study area and to determine if there is any suitable area for the extraction of water resource. To proceed with the study of this area, composed of fractures and dykes, the Very Low Frequency Electromagnetic Method has been used, with which 6 profiles have been made using the ABEM WADI instrument. From these profiles, it was possible to identify two areas with hydrogeological potential, for the emplacement of groundwater catchment soundings.